PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TYPE THE POWER OF TWO BERBANTU VIDEO INTERAKTIF TERHADAP HASIL BELAJAR AKUNTANSI KELAS X SEMESTER GENAP SMK MUHAMMADIYAH 1 METRO TAHUN PELAJARAN 2018/2019 - Dwi Aji Saputri; Ningrum Ningrum; Wakijo Wakijo (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2021)
The problem in the research conducted by researchers, namely "There Are Many Students Who Have Not Experienced in Complete Learning Outcomes of Learning Outcomes of Students in Class X Metro Muhammadiyah 1 Metro Year 2018/2019 Academic Year". From the problem, eating the problem statement is "Is There an Effect of Cooperative Learning Type Model Strength Two Helping Interactive Videos Against Accounting Learning Outcomes of Students of Class X Metro Muhammadiyah 1 Metro Year 2018/2019 Academic Year"? The purpose of this study was to determine the effect of using the Cooperative Learning Model Type The Power of Two Helps Interactive Videos Against Accounting Results in Class X of the Muhammadiyah Metro 1 Vocational High School 2018/2019 Academic Year. So the hypothesis in this study is as follows: "There is the influence of the use of Cooperative Learning Learning Type Strength Type Two Helps Interactive Videos Against Accounting Results in Class X of Muhammadiyah 1 Metro Vocational Middle School 2018/2019 Academic Year".